2018
DOI: 10.1038/s41598-018-20765-8
|View full text |Cite
|
Sign up to set email alerts
|

The MRPS18-2 protein levels correlate with prostate tumor progression and it induces CXCR4-dependent migration of cancer cells

Abstract: We have earlier found abnormal expression of the mitochondrial ribosomal protein S18-2 (MRPS18-2, S18-2) in endometrial cancer, compared to the expression in hyperplasia and in normal endometrium. Here we report that expression of S18-2 was increased with disease progression in clinical specimens of prostate cancer (PCa). The level of induction of epithelial to mesenchymal cell transition (EMT) correlated with the expression level of S18-2 in PCa cell lines. Moreover, cells acquired increased ability of migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
(35 reference statements)
0
9
0
1
Order By: Relevance
“…We next precipitated human KLF4 from PC3 and PC3-S18-2 cells, a PC3 subline that constitutively expresses high levels of S18-2 ( Fig. 5 B ) ( 20 ). Mouse Klf4 was also precipitated to the S 18–2 promoter region from RH18RB cell lysates ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next precipitated human KLF4 from PC3 and PC3-S18-2 cells, a PC3 subline that constitutively expresses high levels of S18-2 ( Fig. 5 B ) ( 20 ). Mouse Klf4 was also precipitated to the S 18–2 promoter region from RH18RB cell lysates ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…mS18b (MRPS18-2) —mS18b protein levels were found to be elevated in prostate cancer tissue; however, additional mechanistic characterization is required to establish a link between mS18b and cancer [ 131 ].…”
Section: Mitoribosome Biogenesis and Diseasementioning
confidence: 99%
“…Overexpression of MRPS18-B (MRPS18-2) leads to the epithelial cells that acquire a higher migration ability to transform as mesenchymal cell (EMT). Further studies have shown that MRPS18-2 induces EMT through the TWIST2/E-cadherin signal and CXCR4 (PC3 cells express the chemokine receptor) mediates the migration of prostate cancer cells [ 67 ]. Lately, MRPS7 was detected as a key gene in the pathophysiological process of osteosarcoma and the MRPL3 content is positively correlated with the prognosis of osteosarcoma [ 6 ].…”
Section: Mrps Associated With Cancersmentioning
confidence: 99%